Life, death, and corporeal resistance in immigration detention - Moss, Jana Michelle (AUC Knowledge Fountain, 2019)
This thesis analyzes corporeal strategies of resistance used by immigration detainees in the global North. Corporeal resistance is defined as an act of protest that physically harms the actor but is not intended to harm anyone else. Examples include hunger strikes, lip sewing, self-immolation, and other forms of public suicide. In response to the prevailing public opinion that detainees' acts of self-harm or suicide are simply acts of desperation by disenfranchised people who have nothing to lose, I argue that they can be a logical and strategic response to state necropolitics. Detainees take back corporeal necropower by reasserting control of their own life and death. The paper proceeds by analyzing the corporeal power inherent in immigration detention centers. I analyze detention centers as a space of waiting in a confined space for an indeterminate amount of time, in which the state is given the power to deport detainees to a place where their life is threatened (effectively sentencing them to death), or allow detainees to stay (letting them live). I then elaborate on how detainees have used methods of self-harm as a form of corporeal resistance. Narratives from detainees who have participated in these acts demonstrate a desire to reassert corporeal autonomy and send a symbolic message that their life is at stake. State responses to detainee corporeal resistance, in turn, show that these acts are a threat to the very object and purpose of immigration detention.